Maintaining a 'fit' immune system: the role of vaccines. (31st December 2023) - Laupèze, Béatrice; Doherty, T. Mark
ABSTRACT: Introduction: Conventionally, vaccines are thought to induce a specific immune response directed against a target pathogen. Long recognized but poorly understood nonspecific benefits of vaccination, such as reduced susceptibility to unrelated diseases or cancer, are now being investigated and may be due in part to "trained immunity'. Areas covered: We discuss 'trained immunity' and whether vaccine-induced 'trained immunity' could be leveraged to prevent morbidity due to a broader range of causes. Expert opinion: The prevention of infection i.e. maintaining homeostasis by preventing the primary infection and resulting secondary illnesses, is the pivotal strategy used to direct vaccine design and may have long-term, positive impacts on health at all ages. In the future, we anticipate that vaccine design will change to not only prevent the target infection (or related infections) but to generate positive modifications to the immune response that could prevent a wider range of infections and potentially reduce the impact of immunological changes associated with aging. Despite changing demographics, adult vaccination has not always been prioritized. However, the SARS-CoV-2 pandemic has demonstrated that adult vaccination can flourish given the right circumstances, demonstrating that harnessing the potential benefits of life-course vaccination is achievable for all. Graphical Abstract: uf0001